Electrochemical, thermodynamic, surface and theoretical investigation of 2-aminobenzene-1,3-dicarbonitriles as green corrosion inhibitor for aluminum in 0.5 M NaOH - Verma C.B.; Singh P.; Bahadur I.; Ebenso E.E.; Quraishi M.A. (My University, 2025)
Abstract The influence of 2-aminobenzene-1,3-dicarbonitriles derivatives (ABDNs) namely 5′-amino-2,4-dihydroxy-4"-methyl-1,1′:3′,1"-terphenyl-4′,6′-dicarbonitrile (ABDN-1), 5′-amino-2,2",4-trihydroxy-1,1′:3′,1"-terphenyl-4′,6′-dicarbonitrile (ABDN-2) and 5′-amino-2,3",4-trihydroxy-1,3-methoxy, 1′:3′,1"-terphenyl-4′,6′-dicarbonitrile (ABDN-3) on aluminum corrosion in 0.5 M NaOH was investigated using chemical and electrochemical methods. Potentiodynamic polarization study reveals that 2-aminobenzene-1,3-dicarbonitriles were mixed type inhibitors. Adsorption of 2-aminobenzene-1,3-dicarbonitriles on aluminum surface in 0.5 M NaOH follows the Langmuir adsorption isotherm. Adsorption of inhibitors on aluminum surface was studied using SEM and EDX spectroscopy examinations. Quantum chemical calculations support the weight loss and electrochemical observations. © 2015 Elsevier B.V.